The Influence of Training and Development on Employee Performance: A Mediating Role of Job Satisfaction - K.C., Harendra (Journal of Entrepreneurship & Management Studies, 2025)
This study investigates the influence of training and development on employee performance within the employees of communication sector (NTC and Ncell) of Karnali Province, Nepal. It seeks to understand how training and development programs contribute to workforce efficiency and effectiveness, with a particular focus on the mediating role of job satisfaction. A causal-comparative research design was used in this study. Out of 400 questionnaires distributed, 355 were returned and used for analysis through convenience sampling. The participants were employees from Nepal Telecom and Ncell working in Karnali Province. A structured questionnaire with reliable measures (Cronbach’s Alpha above 0.70) was used to assess training and development, job satisfaction, and employee performance. Partial Least Squares Structural Equation Modelling (PLS-SEM) was applied to examine the direct relationships between the variables and to test whether job satisfaction played a mediating role. The results indicate that training and development significantly and positively influence employee performance, both directly and indirectly, with job satisfaction acting as a mediating factor. This underscores the dual role of training programs in enhancing employee skills and fostering job satisfaction, which in turn boosts overall performance. The study concludes that training and development are critical drivers of employee performance in the communication sector. The use of convenience sampling and the focus on a single geographical region and sector may restrict the generalizability of the findings. Future studies could apply probability-based sampling and examine other sectors or provinces for broader insights. This study contributes to the literature by examining the training-performance relationship with job satisfaction as a mediating variable in the context of a developing economy. It underscores the essential role of well-designed training programs in cultivating a skilled, motivated, and satisfied workforce. The findings recommend that managers implement tailored training programs and foster a learning culture, while policymakers should support skill development initiatives, improve infrastructure, enforce fair labor practices, and promote local employment to ensure sustainable sector growth and regional economic advancement in Karnali Province.